The Challenges of Security Agencies on Jos North Crisis: Interrogating the Nigerian Security Architecture and Capacity for Conflict Management and Peace Enforcement. - Adetoye, Dele; Osunrayi, Folorunso (Advances in Social Sciences Research Journal, 2016)
This study interrogates the causes and course of the protracted conflicts among the various sub-ethnic and lingua-cultural groups in Jos North Local Government area of Plateau State in Nigeria. It examines the interplay of ethnic composition and configuration of settlement pattern[s], migration dynamics, colonial policies, psychological issues that conflate in the region that eventuate in virulent, intermittent, and violent conflicts since 1994. The conflict actors in this area are the Hausa-Fulani, Fulani Herdsmen, popularly known as ‘Bororo’, Afizere, Anaguta, and the Berom. The study also examines the challenges posed to the nation’s security community and the factors responsible for the failure in combating the intractable increasingly protracted conflict. The work is an explorative, micro and empirical study. It adopts the social survey design, as data were drawn from the people in respect of their beliefs, attitudes, and understanding of the conflict. Questionnaires were distributed to respondents in the study area. Other methods employed by the study are interactive methodologies, such as, Focus Group Discussion, Key Informants Interviews and Participatory Rural Assessment. The study identifies political exclusion, pervasive extreme poverty, fear of domination and deprivation of the indigenes by the settlers, that is, the [Hausa-Fulani], dissatisfaction of indigenes with the sociopolitical system, religion as a tool of mobilization for violence etc. as some of the factors responsible for the conflict. The study also finds out that the security agencies, particularly, the Department of State Security, is encumbered by inadequate numerical strength, ineffective deployment of security agents when the need arises, inadequate technical operations, emotional and sentimental attachment of security agencies and government officials in the ethno-religious crises, insufficient inter-agency collaboration and the failure of state actors to respond promptly and appropriately on early warning signs and intelligence reports at critical periods of the Jos North crisis. The study concludes that appropriate interventions in the areas of poverty alleviation/empowerment programmes through capacity building and skill acquisition for the residents, mass education and enlightenment, and dispassionate implementation of reports and recommendations of various investigative panels on the conflicts, would go a long way to resolve the lingering and destructive crisis. The security architecture of the country should also be reviewed with a view to making it more effective and proactive.